Evolving predictive analytics in healthcare : new AI techniques for real-time interventions - Kumar, Abhishek, 1989-; Dubey, Ashutosh Kumar; Bhatia, Surbhi, 1988-; Kumar, Swarn Avinash; Le, Dac-Nhuong, 1983- (The Institution of Engineering and Technology, 2022)
This book examines machine learning trends in predictive technology to solve real-time healthcare problems. By using real-time data inputs to build predictive models, this new technology can model disease progression, assist with interventions or predict patient outcomes.
Keywords: Artificial intelligence -- Medical applications.; Predictive analytics.; elektronické knihy; electronic books